Initial Validation of the Activity Choice Index Among Overweight Women. Issue 2 (2nd April 2016) - Mullen, Sean P.; Silva, Marlene N.; Sardinha, Luís B.; Teixeira, Pedro J.
Abstract : Purpose: This prospective study was designed to evaluate psychometric properties of the Activity Choice Index (ACI), a measure for assessing one's choice to engage in more effortful, physically active behaviors in the course of daily routines over less-demanding, sedentary behaviors, in a sample of overweight women.Method: The sample included 192 overweight women ( M age  = 37.6 ± 7 years; M body mass index  = 31.6 ± 4.1 kg/m 2 ) who were assessed at baseline and 12 months after beginning a weight management intervention.Results: The unidimensional factor structure was confirmed for the 6-item version of the ACI. Group invariance and temporal invariance were also established. Moreover, ACI scores were positively correlated with self-reported physical activity (as measured by the 7-Day Physical Activity Recall), daily pedometer steps, and 3-day average accelerometer counts.Conclusions: This preliminary investigation provides evidence that a relatively brief self-report instrument for assessing lifestyle physical activity choices has strong psychometric characteristics although convergent evidence is limited. The ACI has potential utility for researchers and practitioners aiming to quantify, or track change in, physical activity in everyday, free-living conditions. This early investigation sets the stage for future research to further delineate and strengthen the measurement of the ACI construct.